2021
DOI: 10.22452/ajba.vol14no1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Safety Climate and Employee Engagement towards Organisational Citizenship Behaviour of Sewage Workers

Abstract: Manuscript type: Research paper Research aims: This study aims to investigate the effects of safety climate and employee engagement on organisational citizenship behaviour (OCB). Design/Methodology/Approach: Drawing from the social exchange theory and flow theory, a theoretical framework was developed and tested using data collected from 610 freelance sewage workers. A questionnaire survey was used to collect the data, while structural equation modelling (SEM) analysis was used as the data analysis approach. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The items for each variable, including the independent, mediation, and dependent variables, were adapted from earlier studies. (Tofighi et al, 2018;Maryam et al, 2021) with slight modifications. Meanwhile, this study measured Organizational Commitment through affective commitment, continuance commitment, and normative commitment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The items for each variable, including the independent, mediation, and dependent variables, were adapted from earlier studies. (Tofighi et al, 2018;Maryam et al, 2021) with slight modifications. Meanwhile, this study measured Organizational Commitment through affective commitment, continuance commitment, and normative commitment.…”
Section: Methodsmentioning
confidence: 99%
“…While the research conducted by Maryam et al (2021); Cheng et al (2015); Chang et al (2015); Jo & Lim (2009); Denison & Mishra (1995); Eisenberger et al (2002); Florence & Christian (2003); Folger & Konovsky (1989) that learning organization has a negative and insignificant effect on the behavior of organizational members. Research conducted (Prasetio, 2016;Astuti et al, 2021;Demirel et al, 2018) states that learning organization has a positive and significant effect on the behavior of organizational members, Gomes et al (2021) state that there is a positive relationship between work-life balance and learning organization.…”
Section: Introductionmentioning
confidence: 99%
“…Organizational dehumanization (Caesens and Brison, 2023), organizational security (Liu et al, 2020), organizational support (Liu, Yang, and Mei, 2021), and organizational citizenship behavior (Maryam et al, 2021) are among the topics that are studied in the organizational behavior literature associated with the concept of safety behavior. In the studies conducted on the aviation sector sample, safety behavior is related to organizational trust and organizational commitment (Liu, Yang, and Mei, 2021), organizational safety climate (Maneechaeye and Potipiroon, 2022), and self-efficacy (Chen and Chen, 2014).…”
Section: Safety Behaviormentioning
confidence: 99%
“…Work Engagement is an essential factor on explaining OCB, and cross-lag analysis has offered evidence to support this relationship. (Lee et al, 2018;Maryam et al, 2021) showed that Work Engagement was crucial for OCB growth and for lowering unproductive workplace behavior. Similarly, Work Engagement was found to increase employees' OCB.…”
Section: The Effect Of Work Engagement On Organizational Citizenship ...mentioning
confidence: 99%